A comparative study between continuous and x-interrupted sutures in emergency midline laparotomies - V., Shashikala; S. B., Abhilash; G., Abhishek; Fernandes, Prajwal S. (International Surgery Journal, 2018)
Background: Midline laparotomy is the most common technique of abdominal incisions in both emergency and elective settings. Wound dehiscence is related to several factors pertaining to patient besides suture material and method of closure. This study tries to compare continuous sutures with x-interrupted sutures in mass closure of midline laparotomy wound in patients undergoing emergency midline laparotomy for acute peritonitis. Methods: A total of 60 patients undergoing emergency midline laparotomy for secondary peritonitis were considered for the study, 30 of whom underwent closure of abdominal wall with continuous sutures (Group A) and the other 30 with x-interrupted sutures (Group B) using non-absorbable, monofilament, polypropylene suture. Necessary preoperative data, the time required for rectus closure, length of the suture material required, post-operative complications like surgical site infection, wound dehiscence were analyzed. Results: The groups were comparable in means of age and sex distribution. Group A was found to have lesser time for closure of rectus, lesser suture length and lesser suture to wound length ratio when compared with Group B. Surgical site infections were similar in both groups. Patients with rectus sheath sutured in x-interrupted sutures (n=2) had significantly less wound dehiscence as compared with continuous sutures (n=8) (p<0.05). Conclusions: Interrupted -X suture method of suturing reduces post-operative wound dehiscence, although requires more suture and consumes more time than the continuous method of suturing.